Working with Men in Health and Social Care. - Featherstone, Brid (Sage Publications, 2007)
This is an important and timely book that introduces the complex issues and debates involved in working with men in a range of professional settings. The authors locate academic and popular discourse on masculinities within the specific context of health and social care settings, critically analysing the theory and policy that underpin and inform practice, and continually linking theoretical frameworks to 'real-life' practice examples.